THE POSSIBLE CRUCIAL IMPACT OF COVID-19 OUTBREAK ON WORLDWIDE EDUCATION SYSTEM: PREDICTIVE MODEL THROUGH DATA MINING METHOD (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The outbreak of COVID-19 as a global pandemic has affected several walks of life including the education sector in a global scale. With the seizure of the standard approach of physical classes, internet-based alternative approach of teaching-learning strategy has been employed to continue the academic curriculum. This work is based on the study of the student feedback from the internet-based education policy. In this paper we have presented an approach to analyse the feedback by calculating the modularity of the responses as an optimisation of data mining techniques. Further we have presented the modularity graphs for each of the question used in the survey individually as a strategy analyse the responses from the students about their feedback and opinion regarding the implementation of alternative teaching-learning approach, that may be considered as a useful tool to analyse the student satisfaction level index.